LINGUOCULTURAL ASPECTS OF TEACHING FOREIGN LANGUAGES IN EDUCATIONAL CONDITIONS - Rahmonova, Saodat (Журнал иностранных языков и лингвистики, 2023)
In the theory and practice of foreign language teaching, the problems of the relationship between language and culture, the introduction of the cultural component of the country countries in which the language is learned into the educational content and the associated strengthening of their cultural orientation have been dealt with in numerous studies and publications included.